KAJIAN KOMPARATIF TENTANG CUTI PRESIDEN PETAHANA PADA KAMPANYE CALON PRESIDEN MENURUT UU RI NOMOR 42 TAHUN 2008 TENTANG PEMILU PRESIDEN DAN WAKIL PRESIDEN DENGAN UU RI NOMOR 7 TAHUN 2017 TENTANG PEMILU - Hendra Permadi; Hafiz Sutrisno; Yuli Heriyanti (Pahlawan Tuanku Tambusai University, 2022)
This study discusses the arrangement of the incumbent President's leave between Law Number 42 of 2008 concerning the General Election of the President and Vice President and Law Number 7 of 2017 concerning General Elections, and laws that have principles and a sense of justice according to the Constitution of the State. Republic of Indonesia in 1945. The purpose of this study is to determine the difference between the leave arrangements for the incumbent presidential candidate in the 2009 and 2019 presidential elections and the fairness between the two arrangements. This type of research is normative research. There are differences and similarities in the arrangements for the incumbent's leave, namely the legal basis, implementation, the flexible nature of the rules, the duration of leave, and the ability of the incumbent President-Vice President candidate to take leave simultaneously. Law Number 7 of 2017 provides space for incumbent candidates to be flexible in carrying out their responsibilities and duties and to give campaign time on holidays without leave, principles and a sense of justice according to the 1945 Constitution of the Republic of Indonesia are contained in Law Number 7 of 2017. Keywords : Comparative Study, Incumbent Presidential Leave, Campaign, Presidential Candidate, Justice.